Obstructive sleep apnoea in pycnodysostosis: A three‐dimensional upper airway analysis. (10th January 2022) - Ferlias, Nikolaos; Gjørup, Hans; Doherty, Mia Aagaard; Haagerup, Annette; Pedersen, Thomas Klit
Abstract: Aim: To assess the upper airway (UA) morphology in patients with pycnodysostosis with a 3D analysis, compare results with normative data and investigate the correlation of the total volume (TV) with other UA morphology variables. Materials and methods: Cone beam computed tomography (CBCT) images of eight Danish patients with pycnodysostosis (4 males and 4 females with a mean age of 31.8 years, SD: 16.3 years) were analyzed using Mimics ® (Materialise ® ) and compared with a sex‐ and age‐matched control group (6 males and 8 females with a mean age of 33.6 years, SD: 18.6 years). Results: The distance from the tip of the epiglottis (E) to the Frankfurt horizontal plane (Fp) was significantly shorter in the pycnodysostosis group ( P  < .042). Regarding the cross‐sectional measurements, at the 'maximum constriction' ( P  < .005), the 'upper airway limit' ( P  < .001) and the 'lower airway limit' ( P  < .035) cross‐sections were significantly smaller in the pycnodysostosis group. The volumes 'nasopharynx' ( P  < .002) and 'total airway' (TV) ( P  < .01) were also significantly smaller. Conclusion: Patients with pycnodysostosis have a reduced total airway as well as nasopharyngeal volume compared with matched controls. Additionally, they have a reduced cross‐sectional area in the upper and lower borders of the UA, and the area of maximum constriction is also reduced. These factors might explain the high prevalence of obstructive sleep apnoea in pycnodysostosis. Total airway is positively correlated with total length and cross‐sections at all levels including the maximum constriction area as well as the anteroposterior dimension at the upper and lower airway borders.